Encholirium deodorinae (Bromeliaceae, Pitcairnioideae): a new species with bicolored sepals from the Espinhaço Mountain Range, Minas Gerais, Brazil - Martins, Suzana Ehlin; Tank, Karl-Heinz (Phytotaxa, 2026)
A new species, Encholirium deodorinae, endemic to the Campos Rupestres of the Espinhaço Mountain Range (municipality of Itacambira, Minas Gerais State, Brazil), is described, illustrated, and compared with four morphologically similar species: E. viridicentrum, E. agavoides, E. magalhaesii, and E. irwinii. The new species is distinguished from other species of the genus by a unique combination of characters, including recurved to reflexed leaves, the central ones grayish-green and the older ones turning reddish; inflorescence with subsessile, densely arranged flowers; bicolored sepals (green basally and brown apically); exserted stamens and stigma, the stigma positioned below the anthers; brown floral bracts; a short fertile portion of the inflorescence in relation to the peduncle length (approximately 1:4–9); and floral bracts and sepals frequently bearing dendritic trichomes—an unusual feature in the genus. It differs from E. viridicentrum, the morphologically most similar species, by its shorter fertile portion of the inflorescence and longer peduncle; brown to stramineous floral bracts (vs. green to stramineous); bicolored sepals (green proximally and brown distally vs. uniformly green or green or with light brown apical spot); and the stigma positioned below the anthers at anthesis (vs. above the anthers). According to IUCN criteria, the species is preliminarily assessed as Critically Endangered (CR) due to its extremely narrow endemism and exposure to severe environmental pressures including habitat degradation and climate change impacts.